Acute myeloid leukemia: Comparing French-American-British classification with immunophenotype and cytogenetics - Mekhala Rao; Girish Kamat; Deepak Goni; Girish Balikai (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Acute myeloid leukemia (AML) is a heterogeneous disease as it affects multiple lineages of hematopoietic cells. AIMS AND OBJECTIVES: This study aims to (1) evaluate the immunophenotypic findings of AML patients, (2) correlate the morphological subtypes of AML according to French-American-British classification with immunophenotypic findings, and (3) correlate the immunophenotypic findings in AML patients with findings in cytogenetic studies. MATERIALS AND METHODS: The present study was a cross sectional study. Seventy three patients with a final diagnosis of AML, whose immunophenotyping and/or cytogenetic study results were available, were included in the study. RESULTS: Twenty one (31.81%) out of 66 patients with AML aberrantly expressed lymphoid antigens. The lymphoid antigens expressed were CD7, CD19, TdT, and CD5 which were found in 13 (19.69%), 9 (13.6%), 2 (3%), and 1 (1.51%) patient, respectively. Two out of three patients with t(8;21)(q22;q22) had CD19 aberrant expression. This association was found to be statistically significant with the Fisher exact test, with a statistic value of 0.0277 (P < 0.05). Co expression of two lymphoid antigens such as CD7 and CD19 was associated with monosomy 7 and was found to be statistically significant with a Fisher exact test, with a statistic value of 0.0217 (P < 0.05). In our study, t(8;21) (q22;q22) was found in AML M2 and AML M1. Many of the patients in our study were diagnosed as acute leukemia by morphological evaluation and were not diagnosed as AML. However, immunophenotyping and cytogenetics helped in getting final diagnosis of such patients. CONCLUSION: In conclusion, this study highlights the importance of morphological, immunophenotypic, and cytogenetic evaluations in the diagnosis of AML.